2014
DOI: 10.1111/jam.12547
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of a PatagonianPichia kudriavzeviifor wine deacidification

Abstract: Aims The purpose of this study was to select autochthonous yeasts with metabolic ability to degrade L‐malic acid for its potential use in young wine deacidification. Methods and Results Fifty seven Patagonian nonSaccharomyces yeast of oenological origin were identified by conventional molecular methods and tested in their capability to grow at the expense of L‐malic acid. Only four isolates belonging to Pichia kudriavzevii species showed this property, and one of them was selected to continue with the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 47 publications
0
33
0
1
Order By: Relevance
“…Other members of this genus have also been been recently tested to produce wines with distinctive volatile composition and/or sensory profile. P. kudriavzevii has shown potential to deacidify wine reducing malic acid concentration; at the same time these wines showed higher scores for 'fruit' and 'cooked pears' sensory attributes compared with those using S. cerevisiae alone (del Monaco et al, 2014). Like M. pulcherrima, P. fermentans has also been shown to produce increased concentrations of mannoproteins in laboratory trials in synthetic must and may therefore also have potential in enhancing wine taste and mouth-feel (Domizio et al, 2014).…”
Section: Pichia Sppmentioning
confidence: 98%
“…Other members of this genus have also been been recently tested to produce wines with distinctive volatile composition and/or sensory profile. P. kudriavzevii has shown potential to deacidify wine reducing malic acid concentration; at the same time these wines showed higher scores for 'fruit' and 'cooked pears' sensory attributes compared with those using S. cerevisiae alone (del Monaco et al, 2014). Like M. pulcherrima, P. fermentans has also been shown to produce increased concentrations of mannoproteins in laboratory trials in synthetic must and may therefore also have potential in enhancing wine taste and mouth-feel (Domizio et al, 2014).…”
Section: Pichia Sppmentioning
confidence: 98%
“…Previous isolation of C. ethanolica and C. tropicalis have been reported from damaged plant tissue of oil palm tree [28] and this could be the source of the organism in the drink. Although their role in palm wine fermentation has not been well defined, Pichia species are associated with wine production [29] and can produce important levels of glycerol, which increases the fruity aroma of wines [30]. It has been reported that C. tropicalis is a common spoilage yeast [31] and a biofilm former [32] which may enable it to persist in the palm wine production environment.…”
Section: Diversity Of Yeastsmentioning
confidence: 99%
“…For this reason, our objective was to characterize a culture medium based on red apple bagasse and to test its use for the biomass production of indigenous yeasts of Comahue region belonging to the species S. cerevisiae and P. kudriavzevii , with proven aptitude for oenological use (del Mónaco et al . ,b, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a globalized international market with oversupply, high quality and regularity are essential conditions to maintain and improve competitiveness in the niches already won and to captivate new ones (del Mónaco et al . 2014a).…”
Section: Introductionmentioning
confidence: 99%